The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1029/2020ja028724
|View full text |Cite
|
Sign up to set email alerts
|

On the Generation of an Unseasonal EPB Over South East Asia

Abstract: An unseasonal equatorial plasma bubble (EPB) event over South‐East Asia was observed on July 22, 2014 that has not been studied before. An investigation into this event is presented with the 26th July, 2014 as a comparison, non‐bubble day. The 22nd July EPB event occurred in the late post‐sunset sector and was associated with a small upward plasma drift. This event was highlighted using a new filter on the SCINDA S4 data. Ionosonde data show that sporadic E was present during the growth period for the EPB even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Many papers have employed the use of GPS ground station data, UHF ground station data, ionosonde data, and/or Constellation Observing System for Meteorology, Ionosphere, and Climate (COSMIC) Radio Occultation (RO) data. The results in Currie et al (2021) showed a clear example of an EPB that was missed in GPS ground data in previous studies. Further analysis of the data to include low elevation angles highlighted the event, and other data sets were used to verify the presence of other EPB indicators, confirming that the enhanced scintillation was not contamination from multipath effects.…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations
“…Many papers have employed the use of GPS ground station data, UHF ground station data, ionosonde data, and/or Constellation Observing System for Meteorology, Ionosphere, and Climate (COSMIC) Radio Occultation (RO) data. The results in Currie et al (2021) showed a clear example of an EPB that was missed in GPS ground data in previous studies. Further analysis of the data to include low elevation angles highlighted the event, and other data sets were used to verify the presence of other EPB indicators, confirming that the enhanced scintillation was not contamination from multipath effects.…”
Section: Introductionmentioning
confidence: 68%
“…The results in Currie et al. (2021) showed a clear example of an EPB that was missed in GPS ground data in previous studies. Further analysis of the data to include low elevation angles highlighted the event, and other data sets were used to verify the presence of other EPB indicators, confirming that the enhanced scintillation was not contamination from multipath effects.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…First, it is worth mentioning that a moderate geomagnetic storm occurred in the late hours of 14 January, with Dst reaching −91 nT and Kp reaching 6- (Le et al, 2022). A useful way to analyze temporal changes in ionograms is by representing the data in a format similar to a "range-time-intensity" plot (Carter et al, 2018;Currie et al, 2021;Pradipta et al, 2015). Instead of using total power, Pradipta et al (2015) integrated over the dBm amplitudes across all sounding frequencies, effectively creating a sum of digitized echoes.…”
Section: Resultsmentioning
confidence: 99%